Tissue factor, factor VIII and IX in microvesicle-induced thrombosis and tumor growth of pancreatic cancer - Sheng-Chieh Chou; Shu-Lun Chang; Cheng-Yeh Yu; Chao-I Lin; Yen-Ting Chang; Li-Fu Chen; Jia-Yi Li; Chen‑Hsueh Pai; Shu-Rung Lin; Wern-Cherng Cheng; Chang-Tsu Yuan; Shu-Wha Lin (Thrombosis Journal)
Abstract Background Tissue factor (TF)-rich cancer microvesicles are correlated with thrombosis risk. Intrinsic coagulation factors are also associated with the risk of thrombosis in cancer patients. This study explored the roles of pancreatic cancer-derived microvesicles and intrinsic factors in thrombogenesis. Methods Human pancreatic cancer cell lines rich in TF (AsPC-1-TFhigh, MIAPaCa-2-TFhigh) or poor in TF [AsPC-1-TFKO(knockout) and MIAPaCa-2-TFlow] were generated for microvesicle preparation and injected into coagulation-defective mice. Inferior vena cava (IVC) clots and lung thrombosis were evaluated. Immunodeficient hemophilia A (NSG-HA) mice were orthotopically injected with the cells mentioned above, and the tumor and IVC clot weights were analyzed. Results With the injection of TFhigh microvesicles, IVC clots were rarely found in hemophilic mice. The TFlow and TFKO microvesicles resulted in few IVC clots in any mouse. Lung thrombosis was substantially reduced in the hemophilic mice infused with any microvesicle type. In orthotopic tumor models, TFhigh cells grew faster than did TFlow cells. TFhigh tumor-bearing NSG-WT mice had the most enormous IVC clots, whereas NSG-HA mice had no IVC clots. Conclusion Pancreatic cancer thrombosis induced by TF-expressing microvesicles strongly depended on FVIII and FIX, while VWF played a minor role. Moreover, TF, but not FVIII, was significantly related to tumor growth.